2000
DOI: 10.1063/1.874002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamics stability of compact stellarators

Abstract: Recent stability results of external kink modes and vertical modes in compact stellarators are presented. The vertical mode is found to be stabilized by externally generated poloidal flux. A simple stability criterion is derived in the limit of large aspect ratio and constant current density. For a wall at infinite distance from the plasma, the amount of external flux needed for stabilization is given by F i = (κ 2 − κ)/(κ 2 + 1), where κ is the axisymmetric elongation and F i is the fraction of the external r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The development of a second kink stabilization scheme-a three-dimensional corrugation of the plasma boundary with little associated shear-to augment externally generated shear is therefore key to generating attractive kink-stable configurations for NCSX. 5,14 The stabilizing corrugation is illustrated in Fig. 3, which shows the cross section of the reference configuration at several values of the toroidal angle, as well as the cross section of a closely related kink-unstable configuration.…”
Section: A Quasi-axisymmetric Plasma Configurationsmentioning
confidence: 99%
“…The development of a second kink stabilization scheme-a three-dimensional corrugation of the plasma boundary with little associated shear-to augment externally generated shear is therefore key to generating attractive kink-stable configurations for NCSX. 5,14 The stabilizing corrugation is illustrated in Fig. 3, which shows the cross section of the reference configuration at several values of the toroidal angle, as well as the cross section of a closely related kink-unstable configuration.…”
Section: A Quasi-axisymmetric Plasma Configurationsmentioning
confidence: 99%
“…We asked, moreover, that the rotational transform supplied by rippling the boundary alone be of certain shape and magnitude (for the baseline, monotonically increasing and of magnitude 0.45), that the transform increases as radius increases, and that there exists a magnetic well in the absence of the plasma pressure. Although recent results from W7AS and LHD showed that the linear, ideal MHD theories have limited applicability in predicting the stability limit in stellarators, we still included the stability to the infinite-n ballooning and ideal external kink modes calculated based on such theories as constraints in the optimization since in the NCSX studies we found that including, for instance, the external kinks as a constraint the structure of local shears would respond in such a way that the resulting configuration would generally have more favorable MHD stability characteristics [23]. However, we did not strictly enforce such constraints and in some advanced configurations these constraints were relaxed considerably, as suggested by the nonlinear theory [24].…”
Section: Physics Design and Optimizationmentioning
confidence: 99%
“…All of the configurations explored have large axisymmetric (or toroidal average) elongation and triangularity, to enable good stability to ballooning and kink modes. The vertical mode (n=0) is calculated to be robustly stable [22], allowing consideration of average elongations up to 3.…”
Section: Configuration Design and Stabilitymentioning
confidence: 99%